Pembuatan Video Promosi Perpustakaan Layanan Anak di Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Wari, Nindy Perdana; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
AbstractA making library promotion video and reading for children in Dinas Perpustakaan dan Kearsipan Provinsi Sumatera Barat,, to promote library especially children service in order to optimize library usage in growing reading interest to society which expected to start from early age. Making this research using descriptive methods, by way of observation. After the data collection is done, the next step in the library promotion and reading for children is (1) pre production by determining the idea, making synopsis, treatment, storyboard, shooting script, production planning, production preparation, and the last is editing vidio, (2) production, production stage, production stage is the stage used to run all the stages that have been designed at the stage of pre-production, (3) post production vidio production using video editing software is Adobe Pemier Pro Software.Keyword: making, video, promotion, library